Body Image, Stigmatization, and Life Quality among Young Women with Acne Vulgaris - Sarwar, Ayesha; Shahed, Sarah (Journal of Development and Social Sciences, 2024)
This study examines the relationship between body image, stigmatization, and quality of life among women diagnosed with acne vulgaris. Acne is very commonly occurring chronic inflammatory skin disease affecting people of different ages worldwide. It can affect many parts of the body, mostly the face, chest, and back, and can have a substantial negative impact on a person’s quality of life. 150 women were approached from dermatology departments of hospitals in Lahore. Measures included Demographic Sheet, Body Image Scale, Stigmatization Scale, and Dermatology Life Quality Index Questionnaire. The results showed that Body image, stigmatization, and quality of life were significantly correlated in females diagnosed with Acne vulgaris. Secondly, body image and stigmatization predicted the Quality of life in females with Acne vulgaris. This study can be helpful for psychologists and counselors in planning interventions for individuals with acne vulgaris who experience poor body image, poor quality of life, and stigmatization.